Myths busted! : just when you thought you knew what you knew-- - Krieger, Emily; Cocotos, Tom Nick (Washington, D.C. : National Geographic, 2013)
Explains the truth behind popular myths and urban legends.
Includes index.
7.2
3-6
3-6
Keywords: Common fallacies -- Juvenile literature; Common fallacies; Errors; Errors